First Congress of the Quechua language and Aymara language: (Cusco, February 13-15, 1987) - Allpanchis, Revista (1987)
The Work Commission No. 01.A on the Quechua Alphabet, chaired by Prof. Clodoaldo Soto Ruiz, consulted the opinion of the consensus, delegation, on the use of 3 or 5 vowels, whose result was a tie, according to the Secretary of the Commission Prof. Luis Enrique López, a result that was questioned by the Delegate of the Academy of Aboriginal Languages ​​Rubén Muñoz Hermoza and other Delegates, moments in which the Members of the Work Commission No. 01 resign and abandon their functions in the presence of Congress in plenary that was two hours late.